Immunoglobulin chain loss in hybridoma lines. - Köhler, G (1980)
Hybrid cells secreting one, two, or three different immunoglobulins were constructed. The loss of immunoglobulin heavy or light chain expression was monitored. Chain loss was random only in lines with an excess of active light chain genes over heavy chain genes. In all other combinations preferential heavy chain loss was observed. Variant cells altered in heavy or light chain synthesis exhibited an altered chain loss pattern. It is therefore proposed that free immunoglobulin heavy chain is toxic for the cells. The interdependence of the two gene products gives a possible molecular explanation of apparent directed chromosome loss in hybrid cells.